The Efficiency of Ideology and the Possibilities of Art: An Althusserian Account - Pfaller, Robert (Stasis, 2016)
Louis Althusser’s theory of ideology allows us to account for all kinds of joyful obedience performed by individuals. This theory does not require any assumption of lacking knowledge or “false consciousness” on the side of subjectivated individuals. Therefore, it provides the crucial tools for explaining the specific political efficiency of art. This efficiency does not stem from any new “information,” as the predominant tendencies in alleged “political” or “documentary” art since the 1990s have presupposed, and as the popular notion of “artistic research” may still suggest. On the contrary, in order to be politically efficient, art has to tackle not the knowledge but the specific subjectivations individuals have undergone. When one augments Althusser’s fragmentary account of subjectivation by the distinctions between “belief” and “faith” introduced by Octave Mannoni, and additionally introduces as a third category that of “paranoia,” then one can specify the predominant types of subjectivation in current Western societies—as well as the exits that critical art can offer from these subjectivations. Artistic exit strategies from forms of faith and paranoia will be analyzed with regard to works by John Heartfield, Bernard Mandeville, and Christoph Schlingensief.